Chinese Cultural and Opera Stage Architectural Design for Urbanization Henan, China - Chen, Chen; Arus, Baharudin Bin Mohd (South Asian Journal of Social Sciences and Humanities, 2024)
Background and Purpose: Urbanization in Henan, China has rapidly transformed the  landscape, posing challenges to preserving traditional cultural elements like Chinese cultural  and opera stages. This study aimed to provide qualitative insights into integrating traditional  cultural/opera architectural design with modern urban development in Henan. Methods: Semi-structured interviews were conducted with 10 Henan residents to gather  perspectives and experiences. Interview data was thematically analysed. Findings: Residents highly valued traditional cultural/opera stage design, indicating strong  cultural interconnectedness. However, challenges were identified including commercial  pressure in development, implying difficulty balancing economic growth and cultural  preservation. Community participation was mixed with some active engagement.  Environmental sustainability concerns and financial/institutional capacity constraints  highlighted the need for collaborative approaches.  Conclusion and Implications: Traditional cultural elements retain deep meaning for Henan  residents amidst rapid urbanization. Preserving these traditions while enabling modernization  will require overcoming multiple complex challenges across commercial, environmental,  social, and institutional dimensions. Findings indicate that collaborative, multi-stakeholder  urban planning approaches are needed to integrate cultural preservation with sustainable  growth in Chinese cities undergoing rapid development. Study insights on resident perspectives  and challenges can inform policies and frameworks to effectively balance economic,  environmental, and cultural priorities.
Keywords: Chinese culture; Opera; Architectural design; Urbanization; Henan